Prevalence and Factors Related to Hypovitaminosis D in Type 2 Diabetes Mellitus Patients with Depression - Rudi Putranto; Siti Setiati; Martina W Nasrun; Fiastuti Witjaksono; Suzanna Immanuel; Imam Subekti; Kuntjoro Harimurti; Agus Siswanto; Hamzah Shatri; Suhendro Suwarto (Acta Medica Indonesiana, 2023)
Background: The prevalence of hypovitaminosis D (hypoD) in patients with type 2 diabetes mellitus (T2DM) and depression has not been documented. In addition, the risk factors are unknown. This study aimed to identify the prevalence of and risk factors for hypoD in patients with T2DM who also have depression. Methods: 118 patients with T2DM who visited the outpatient endocrinology clinics at Cipto Mangunkusumo National Hospital between December 2019-September 2022 provided the clinical and demographic data for this cross- sectional study, including body mass index, blood pressure, glycosylated haemoglobin (HbA1c), lipid profiles, therapy, gender, age, marital status, and educational background. We used The Beck Depression Inventory II (BDI II) to evaluate depression. We used enzyme-linked immunosorbent assay kit to assess the dependent variable: serum vitamin D. We characterized serum vitamin D levels into three groups (normal, 30 ng/mL; insufficient, 20-29 ng/mL; deficient, 20 ng/mL). We also used analyses of variance to examine the anthropometric, clinical, and biochemical factors between the three groups. Results: 118 subjects with T2DM. Their median age was 56 years old (48, 75-60 years old), with a BDI II score of 17 (15-19), and a serum concentration of vitamin D. The D level was 18.3 ng/mL (9.17–29.46 ng/mL). Only 21.8% of patients with T2DM and depression had sufficient levels of vitamin D. We used multivariable analysis of variance model to examine the associations between age, BDI II score, HbA1c, and systolic and diastolic blood pressure with vitamin D level. Age and BDI II score both had a statistically significant effect on vitamin D levels. Conclusion: This cross-sectional study discovered that patients with T2DM and depression had a high prevalence (77.7%) of hypoD. Age and BDI II score both affected differences in vitamin D levels with statistical significance.